First Asian validation of ORBI score in predicting in-hospital cardiogenic shock in patients with ST-segment elevation myocardial infarction treated by primary percutaneous coronary intervention. (14th October 2021) - Putra, A; Juzar, D A; Widyantoro, B; Firdaus, I
Abstract: Background: Cardiogenic shock (CS) complicating an acute coronary syndrome still worsening the prognosis with 30-day mortality rates approximating 40–45%, despite improvements in the acute management of ST-segment elevation myocardial infarction (STEMI), particularly the widespread use of timely primary percutaneous coronary intervention (pPCI). The ORBI risk score provides a readily useable and efficient tool to identify patients at high-risk of developing CS during hospitalization following STEMI which may aid in further risk-stratification and thus potentially facilitate pre-emptive clinical decision making. This is essential in developing countries with wide variation in health care facilities, scarce resources and increasing burden of cardiovascular diseases. Purpose: To validate ORBI Score in identifying patients at high-risk of in-hospital STEMI related cardiogenic shock in a multi-ethnic developing country. Method: The ORBI risk score was evaluated in 1934 patients STEMI without CS on admission and treated by primary percutaneous coronary intervention (pPCI) in our national cardiovascular centre included this study. Model discrimination and calibration was tested in the overall population. Eleven variables from the ORBI score were independently associated with the development of in-hospital CS: age >70 years, prior stroke/transient ischaemic attack, cardiac arrest upon admission, anterior STEMI, first medical contact-to-pPCI delay >90min, Killip class, heart rate >90/min, a combination of systolic blood pressure <125 mmHg and pulse pressure <45 mmHg, glycaemia >10 mmol/L, culprit lesion of the left main coronary artery, and post-pPCI thrombolysis in myocardial infarction flow grade <3. The score derived from these variables allowed the classification of patients into four risk categories: low (0–7), low- to-intermediate (8–10), intermediate-to-high (11–12), and high (≥13). Results: Observed in-hospital CS rates were 0.3%, 6.4%, 19.5%, and 32.12%, across the four risk categories, respectively. The score demonstrated high discrimination (c-statistic of 0.91 (CI 95% 0.88–0.93), p<0.001 in the validation cohort) Conclusion: The ORBI risk score is valid and can be used for predicting the development of cardiogenic shock in STEMI patients for better targeted treatment. FUNDunding Acknowledgement: Type of funding sources: None.